Arte urbana grafite em Palmas/TO: uma linguagem artística contemporânea - Santos, Maryelli Coimbra dos (Universidade Federal do Tocantins, 2024)
This course completion work has the general objective of understanding urban graffiti art as an object of culture and a form of contemporary artistic language, and the object is in the visual representations of urban graffiti art present in the city of Palmas, Tocantins. Throughout the development of this article we seek to answer the following question: How does the manifestation of urban graffiti art occur in the city of Palmas/TO. We also highlight the considerations made about the history of graffiti as part of the hip-hop culture that emerged in the mid-1970s, but currently being a relevant form of expression of urban art. The work was carried out based on bibliographical research, with readings in books, articles, theses and dissertations on specialized sites that present the referred theme, also presenting the production of graffiti in public spaces in Palmas, capital of the state of Tocantins. It is concluded that graffiti urban art, unlike pichação, creates environments for reflection and communication, with social recognition around the life of the population.